Coaching competency and trust in coach in sport teams - San-Fu, K.; Ming-Hui, H.; Po-Lun, L. (International Journal of Sports Science & Coaching, 2017)
This study examines the relationship between coaching competency as evaluated by athletes and their perceptions of trust in their coaches. The authors hypothesize that athletes' evaluation of four dimensions of coaching competency is positively related to their trust in their coaches, and that this relationship is stronger at the team level than at the individual level. In total, 438 basketball players (251 males and 187 females) from 34 teams completed the Coaching Competency Scale (CCS) and the trust in the coach questionnaire during the postseason. The hypotheses were tested through hierarchical linear modeling. The analyses revealed that individual- and group-level evaluations of the fourdimensional CCS (motivation, game-strategy, technique, and character-building competencies) positively predicted trust in the coach; furthermore, group-level coaching competency was the primary contributor to this relationship. Therefore, improving the psychological and tactical skills of coaches and their skill detection abilities and instruction at training together with a positive attitude toward sports may help improve the trust of athletes in their coaches. ABSTRACT FROM AUTHOR